Global Business Citizenship and Voluntary Codes of Ethical Conduct - Logsdon, Jeanne M. (Journal of business ethics, 2005)
This article describes the theory and process of global business citizenship (GBC) and applies it in an analysis of characteristics of company codes of business conduct. GBC is distinguished from a commonly used term, “corporate citizenship,” which often denotes corporate community involvement and philanthropy. The GBC process requires (1) a set of fundamental values embedded in the corporate code of conduct and in corporate policies that reflect universal ethical standards; (2) implementation throughout the organization with thoughtful awareness of where the code and policies fit well and where they might not fit with stakeholder expectations; (3) analysis and experimentation to deal with problem cases; and (4) systematic learning processes to communicate the results of implementation and experiments internally and externally. We then identify and illustrate the three attributes of a code of conduct that would reflect a GBC approach. The three attributes are orientation, implementation, and accountability. The various components of these attributes are specified and illustrated, using website examples from six global petroleum companies.